2010
DOI: 10.1002/ep.10497
|View full text |Cite
|
Sign up to set email alerts
|

Persistent aromatic pollutants removal using a combined process of electrochemical treatment and reverse osmosis/nanofiltration

Abstract: The application of a combined electrochemical/ membrane filtration process for treatment of wastewaters containing persistent pollutants was investigated. Phenol and an azo dye (Acid Orange 7, AO7) were used as model pollutants. A boron doped diamond electrode, the state-of-the-art in electrode material, was used as anode in the electrochemical treatment, following previous excellent results obtained with this kind of electrodes in the removal of soluble organic compounds from aqueous solutions. Reverse osmosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…In addition, the application of electrolytes with higher conductivity (i. e. 1.5 μS/cm) reduces energy consumption [98]. The two studies by Santos et al [98] and Hamad et al [36], investigated the cost of the processes by determining energy consumption using the following equations 10 and 11: (10) (11) Where U is potential/ voltage (V), I is applied current (A), t is time (h or min. ), V is treated volume (m 3 ), C o , and C t are initial and final concentrations.…”
Section: Cost Of Electrochemical Processesmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the application of electrolytes with higher conductivity (i. e. 1.5 μS/cm) reduces energy consumption [98]. The two studies by Santos et al [98] and Hamad et al [36], investigated the cost of the processes by determining energy consumption using the following equations 10 and 11: (10) (11) Where U is potential/ voltage (V), I is applied current (A), t is time (h or min. ), V is treated volume (m 3 ), C o , and C t are initial and final concentrations.…”
Section: Cost Of Electrochemical Processesmentioning
confidence: 99%
“…It has been reported [10] that OVIs are a potential risk for the quality and stability of drug products, as well as the human body if intake exceeds the permitted daily exposure (PDE). It is no longer a hidden fact that the wide occurrence of organic contaminants in wastewater poses a severe threat to public health regulatory bodies and ecosystems [11,12]. In view of the above fact, the consensus is that research efforts must be doubled to quickly address the problems, by providing technologies to remediate the contaminated water bodies.…”
Section: Introductionmentioning
confidence: 99%
“…These results showed that the EO process considerably reduced the organic load in the effluent, while a large part of TDS removal was attributed to the final RO treatment. Diogo et al [ 24 ] established a combined electrochemical/membrane filtration process for the treatment of wastewater containing phenol and an azo dye (Acid Orange 7, AO7). A boron-doped diamond (BDD) electrode was used as the anode in the electrochemical treatment, followed by RO and NF membranes, which were used in the concentration step.…”
Section: Coupling Ms and Eaops As A Combined Processmentioning
confidence: 99%
“…Organic impurities such as dyes, alcohols and acids are discharged into potable water sources and consequently causing water pollution . Color of dyestuffs in the wastewater generally becomes the main problem of wastewater treatment due to its serious environmental influences . There are some methods of sewage treatment, such as physical method, biological method, chemical method and so on.…”
Section: Introductionmentioning
confidence: 99%